Sustainable, highly foldable, eco-friendly films from Mandua starch derivative. (October 2022) - Kumar Malik, Mayank; Kumar, Tarun; Kumar, Vipin; Singh, Jaspal; Kumar Singh, Raj; Saini, Karuna
Graphical abstract: Highlights: Starch from mandua grains was isolated using alkali stepping method. Mandua starch was chemically modified using acetic anhydride. Modified mandua starch, alkali isolated starch was characterized by FTIR, SEM, XRD and thermal gravimetrically. Highly foldable film was developed successfully using acetylated mandua starch. The % elongation at break of the acetylated mandua starch was higher than alkali isolated mandua starch film. Acute toxicity analysis confirmed that AC-MS was safe for utilization under 2, 000 mg/kg body weight of animal. Abstract: Starch is a biodegradable biopolymer with great potential for developing novel biodegradable products. However, Starch can be derivatized to improve its functionality and uses. In current research, underutilized mandua grains were used for starch isolation by alkaline stepping method, derivatized using acetic anhydride and characterized by SEM, FTIR, XRD and TGA. Further, the highly moldable, sustainable films of esterified mandua starch were successfully prepared via combining starches with glycerol and polyvinyl alcohol using a film-forming casting technique. The films were characterized for mechanical properties and morphology. The tensile strength of the esterified mandua starch film was significantly lower than those of the alkali isolated mandua starch film with polyvinyl alcohol. Further, acute toxicity study of acetylated mandua starch showed no adverse effect on biochemical parameters of treated animals. The findings demonstrated that the mandua starch films' flexibility was increased after acetylation. Thus, esterified mandua starch films might provide excellent substitutes for developing biodegradable products.